Wheat Varietal Diversification Increases Ethiopian Smallholders’ Food Security for 50,000 to 75,000 farmers: Evidence from a WLE/Alliance-led Participatory Development Initiative - CGIAR Research Program on Water, Land and Ecosystems (2020)
The WLE/Alliance-led Seeds for Needs program developed a new way to evaluate and promote improved seed varieties, and advanced breeding lines. A survey of 1008 households across three Ethiopian states shows the program signiﬁcantly enhanced wheat productivity and smallholders’ food security by increasing varietal diversiﬁcation. The study provides empirical evidence for the effective role varietal diversity can play in improving food security in marginal environments.